PENINGKATAN PERFORMA HASIL PEMBAKARAN MENGGUNAKAN MIXING COMBUSTION CHAMBER PADA KOMPOR BERBAHAN BAKAR BIOGAS MENUJU DESA MANDIRI ENERGI DI YOGYAKARTA - Hariyanto, Kris; Mardwianta, Benedictus (Sekolah Tinggi Teknologi Adisutjipto, 2016)
Biogas is an alternative energy sources as a substitute for fossil fuels in household activities daily, but there are obstacles in the use of biogas, namely the difficulty of arranging a flame that is stable and fuel consumption relatively less efficient biogas. So it takes a design development system that will produce a burning stove produces biogas-fueled stove fits the purpose of research, on the other hand biogas stove should be simple, cheap production price, maximum efficiency and safe to use. Stages in the study include: desk assessment, creation of objective requirements desing, manufacture conceptual and basic design, manufacture real stove. As for knowing the performance of the stove carried ujji stove performance are: test flame stability and efficiency. The results showed that the efficiency of the biogas stove design results in only 31 percent higher than the efficiency of biogas stoves old design, while the fuel consumption of biogas stoves new design is 16 percent lower when compared with fuel consumption of biogas stoves old design. In terms of manufacture and ease of repair and maintenance of gas cookers new design is more easily repaired and easy to make and simple in form compared with the old design biogas stoves.